OCEANOGRAPHIC DATA OF THE 27TH JAPANESE ANTARCTIC RESEARCH EXPEDITION FROM NOVEMBER 1985 to APRIL 1986 - イワナガ, ヨシユキ; トウジュ, ヒロシ; IWANAGA, Yoshiyuki; TOHJU, Hiroshi (National Institute of Polar Research, 1987)
P(論文) This report presents the data of the oceanographic observations on board the icebreaker Shirase and the tidal observation at Syowa Station. The oceanographic observations were carried out in the summer mission of the 27th Japanese Antarctic Research Expedition (JARE-27) in 1985-1986, and the tidal observation was carried out in the winter mission of JARE-26 in 1984-1985. departmental bulletin paper